cDNA Cloning and mRNA Expression of Estrogen Receptor α in Japanese Quail - Kouhei Ichikawa; Ichiro Yamamoto; Akira Tsukada; Noboru Saito; Kiyoshi Shimada (The Journal of Poultry Science, 2003)
The biological actions of estrogen are mediated via estrogen receptors (ER). Although chicken ER cDNA for subtypes α and β have been identified, only the β form of ER cDNA was cloned in quail. Hence, in this study the cDNA of ERα subtype was cloned and levels of mRNA expression were studied in different tissues in quail. Quail ERα cDNA containing the sequence containing the open reading frame (1770bp) encodes the predicted 589 amino acid residues and had high homology to chicken ERα (98.8%). Both RT-PCR and northern blot analyses indicate that relatively higher expression was observed in the liver, ovary, oviduct and testes. Relatively lower expression was detected in adrenal, cerebrum, hypothalamus, gizzard, heart, kidney and intestine by RT-PCR analysis. Conversely, low levels of expression of quail ERβ mRNA was detected in all the examined tissues. The results indicate that ERα subtype plays a predominant role for estrogenic actions in reproduction in quail.